2014
DOI: 10.1155/2014/434987
|View full text |Cite
|
Sign up to set email alerts
|

First Description of KPC-2-ProducingKlebsiella oxytocaIsolated from a Pediatric Patient with Nosocomial Pneumonia in Venezuela

Abstract: During the last decade, carbapenem resistance has emerged among clinical isolates of the Enterobacteriaceae family. This has been increasingly attributed to the production of β-lactamases capable of hydrolyzing carbapenems. Among these enzymes, Klebsiella pneumoniae carbapenemases (KPCs) are the most frequently and clinically significant class-A carbapenemases. In this report, we describe the first nosocomial KPC-2-producing K. oxytoca isolated from a pediatric patient with pneumonia admitted to the intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Unfortunately, no data are available about STs circulating in Venezuela, as none of the hospitals were part of the study in 2010, although the circulation of the bla KPC determinant in Venezuelan hospitals is documented (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, no data are available about STs circulating in Venezuela, as none of the hospitals were part of the study in 2010, although the circulation of the bla KPC determinant in Venezuelan hospitals is documented (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…In July 2012, Nobari et al [17] identified a strain of K. pneumoniae bla KPC gene that was isolated from the urine of a female patient hospitalized in an Intensive Care Unit ward; they reported it as the first case of K. pneumoniae bla KPC gene in Iran. Some cases of K. oxytoca have also been identified and reported in Brazil [20] and Venezuela [21]. A study in Austria reported the identification of 31 strains of KPC-producing K. oxytoca isolated from five patients hospitalized in Intensive Care Unit wards [1].…”
Section: Discussionmentioning
confidence: 98%
“…K. oxytoca is an opportunistic pathogen and is now identified and introduced as an important clinical pathogen that is associated with nosocomial infections in hospitalized patients, including children, newborns, and individuals with immune deficiency [19]. A few studies have reported the identification of the KPC gene in K. oxytoca strains in some countries such as Austria [18], Brazil [20], and Venezuela [21]. Identification of this gene plays an important role in the study of K. oxytoca antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, en este estudio la presencia de estas enzimas fue confirmada mediante la aplicación de los métodos de sinergismo con inhibidores específicos (EDTA-SMA y ácido borónico). El registro de cepas productoras de KPC es escaso en HULA (25) y la presencia de metaloenzimas en enterobacterias no había sido descrita hasta el momento.…”
Section: Discussionunclassified